An Angular Position-Based Tracking Algorithm for Geolocation in Smart Cities Applications - Muniz, Jamerson A.; Paula, Ricardo De Castro; Camargo, Edson T. De (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2024)
Tracking a vehicle in real time usually requires the transmission of the geographical coordinates of its route to the Internet. As part of a partnership to develop smart cities applications, a prototype vehicle tracking system has been developed and evaluated. The algorithm records the geolocation of the vehicle every 30 seconds, which can lead to unnecessary coordinates being sent and the communication network being overloaded. The aim of this work is to develop an algorithm that is able to determine the location of a moving object based on its angular position. The proposed algorithm uses an inertial measurement unit sensor to determine the change of direction and is able to correctly determine the route even if a coordinate is lost. We conducted an experimental study comparing the periodic approach with angular position-based approach on a route of a public bus in the city of Toledo/PR. The results show that the angle-based algorithm reduces the number of transmitted coordinates by up to 30%.